2002
DOI: 10.1093/jnci/94.8.617
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Hormone-Induced, STAT3-Mediated Interleukin 6 Action in Normal and Malignant Human Ovarian Surface Epithelial Cells

Abstract: The IL-6/STAT3 signaling pathway may mediate FSH-, LH-, and estrogen-stimulated HOSE cell proliferation. Increased IL-6Ralpha expression and constitutive STAT3 activation may be associated with ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 62 publications
1
99
1
1
Order By: Relevance
“…Additionally, FSH significantly upregulates the level of protein kinase Cα (PKCα) mRNA and protein, and the PKC pathway has been proposed to play a role in FSH-induced cell proliferation in ovarian cancer cells [27]. FSH also stimulates the growth of human OSE and ovarian cancer cells through the PKA and inerleukin-6/signal transducers and activators of transcription 3 (STAT3) signaling pathway [45]. The present study shows that FSH stimulated survivin expression through activation of the PI3K/AKT signal transduction pathway in SKOV-3 and ES-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FSH significantly upregulates the level of protein kinase Cα (PKCα) mRNA and protein, and the PKC pathway has been proposed to play a role in FSH-induced cell proliferation in ovarian cancer cells [27]. FSH also stimulates the growth of human OSE and ovarian cancer cells through the PKA and inerleukin-6/signal transducers and activators of transcription 3 (STAT3) signaling pathway [45]. The present study shows that FSH stimulated survivin expression through activation of the PI3K/AKT signal transduction pathway in SKOV-3 and ES-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Serum added to the bottom chamber was used as the chemoattractant. At 24 hours after plating, noninvading cells were removed, and invading cells were counted in 5 fields per slide as previously described (37). The assay was run in triplicate.…”
Section: Invasion Assaymentioning
confidence: 99%
“…Cellular extracts were prepared as previously described (37). Briefly, cell lysates were prepared in radioimmunoprecipitation assay buffer, and proteins extracted (20 mg) from each cell culture were separated by electrophoresis on 7.5% or 10% SDS-polyacrylamide gels.…”
Section: Western Blottingmentioning
confidence: 99%
“…Results of multiple studies indicate a pathogenic role of this cytokine in the malignant transformation, progression and chemotherapy resistance of OVCA (Syed et al 2002, Nilsson et al 2005, Rabinovich et al 2007, Yang et al 2009, Wang et al 2010a, 2012. Recently, the results of our studies indicated that IL6 secreted by OVCA cells may contribute to the refractoriness of these cells to TAM via ER isoforms and steroid hormone receptor coactivator (SRC)-1 (Wang et al 2014).…”
Section: Introductionmentioning
confidence: 77%
“…In addition, increased activation of their downstream targets ERK and PI3K/Akt leading to increased pERa-Ser118 and/or pERa-Ser167 have been observed (Gee et al 2001, Yamashita et al 2005, Sarwar et al 2006. It has been widely reported that IL6 plays a critical role in the development and progression of OVCA (Syed et al 2002, Nilsson et al 2005, Rabinovich et al 2007, Yang et al 2009, Wang et al 2012. Recent results from our group indicated that IL6 secreted by OVCA cells may contribute to the refractoriness of these cells to TAM via ER isoforms and SRC-1 (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 98%